Soft skills and inter-disciplinarity as core contents for the education of educative professionals - Maria Cinque; Andrea Dessardo (Firenze University Press, 2020)
It is hard to discern among hard and soft skills as far as the competencies of professional educators are concerned, especially the socio-pedagogic ones, since these are people-oriented professions This assumption is confirmed by the analysis of the study plans and the Year Unique Forms (SUA) of the L-19 BA courses activated by Italian universities.   Competenze trasversali e interdisciplinarità come contenuti core per la formazione dei professionisti dell'educazione È difficile distinguere tra hard e soft skill in relazione alle competenze degli educatori professionali, specie di quelli socio-pedagogici, dal momento che si tratta di professionalità particolarmente orientate al lavoro con le persone. Tale assunto trova conferma dall'analisi dei piani di studio e delle Schede Uniche Annuali (SUA) dei corsi di laurea L-19 attivati negli atenei italiani.